Study of reading habits 1984 - Alingsås - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Alingsås. Many of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. These questions dealt with: the importance of getting news from different areas; opinions on Alingsås Tidning, Göteborgs-Posten and Alingsås Kuriren; and the importance of a number of political goals. The respondents also had to state if they agreed or disagreed with a number of statements on politicians and authorities.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Alingsås. Many of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. These questions dealt with: the importance of getting news from different areas; opinions on Alingsås Tidning, Göteborgs-Posten and Alingsås Kuriren; and the importance of a number of political goals. The respondents also had to state if they agreed or disagreed with a number of statements on politicians and authorities.
Läsvanestudien 1984 - Alingsås
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap